Methodical approaches to the diagnosis of varicocele in children - Muratov A.A; Yusupolieva G.A; Fazylov A.A (Genius Journals, 2021)
The methodological and clinical approaches to ultrasound examination were studied depending on the age groups of children. Improvement of the technology of ultrasound examination of the scrotal organs in case of suspected varicocele. The features of the ultrasound image of varicocele in the gray-scale echography and doppleography modes are presented.
Keywords: Methodology; Varicocele; Ultrasound Features.